THE ROLE OF THE NATIONAL IDEA IN EDUCATING YOUTH IN THE SPIRIT OF MILITARY PATRIOTISM (Web of Teachers: Inderscience Research, 2025)
The article discusses the important role of the national idea in educating young people in the spirit of military patriotism.